LOCAL KNOWLEDGE: TRADITIONAL HEALING PRACTICES NEED TO BE PRESERVED - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 2 February 2016 – Traditional healing practices using ageold techniques need to be given serious attention to prevent such local knowledge from being dismissed in the efforts to develop scholarly knowledge.